Monitoring the water content evolution of dikes - Rings, Jörg (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung der Universität Karlsruhe (TH), 2009)
The water content evolution of model dikes is monitored with geophysical methods. Water content changes are successfully quantified using electrical resistivity tomography. Numerical simulation of water flow in a dike model is used to estimate the variability of water content. Modeling of synthetic data sets is used to evaluate the quality of resistivity quantification using ERT. An ensemble approach is proposed to improve the interpretation of ERT inversions.